Microalbuminuria in Type II Diabetes Mellitus With Good Glycemic Control (Medical Forum Monthly, 2024)
Objective: To determine the frequency of microalbuminuria in Type 11 Diabetes Mellitus with good glycemic control in a tertiary care hospital of KarachiStudy Design: Descriptive / cross sectional study.Place and Duration of Study: This study was conducted at the Department of Internal Medicine, Liaquat National Hospital Karachi from Feb 2018 to July 2018.Materials and Methods: A total of 140patients of type 11 diabetes mellitus with good glycemic controlwere selected. Urine for micro albumin level was sent to the institutional laboratoryto assess microalbuminuria. All the collected information was entered in the prescribed Performa.Results: A total of 140 type 2 DM patients with good glycemic control were included in our study. Out of 140 patients 63 (45%) were female and 77 (55%) were male with mean age of 44.47±4.99 years. Mean duration of DM was 4.21±0.94 years. Mean HbA1c level was 6.897±0.1779. Twelve patients (8.6%) were found to have microalbuminuriaConclusion: Type 11 diabetic patients are at increased risk of developing microalbuminuria even when they have a good or moderately good glycemiccontrol. This complication invariably leads to the development of overt nephropathy over a period of time. In order to prevent this complication, intense Screening protocols should be employed to check for microalbuminuria and HbA1c in both the newly and already diagnosed type 11diabetic, so that the progression of micro and macro vascularcomplications can be halted by timely intervention.